MODELLING AND STATIC ANALYSIS OF DENTAL IMPLANT USING DIFFERENT BIOMEDICAL MATERIALS (International Journal of Food and Nutritional Sciences, 2022)
A Dental implant is a structure that replaces a missing tooth. With screw-likedevices, the surgeoninserts an implant into the jawbone, and it acts as an anchor for anartificial tooth, called a crown. A devicecalled an abutment connects the artificial tooth tothe dentalimplant. The osseointegration of bone andimplant at the interface is of utmost importanceas the success or failure of a dental implant depends on themanner in which stresses aretransferred to the surrounding bone.